2014
DOI: 10.1007/978-3-642-40861-8_64
|View full text |Cite
|
Sign up to set email alerts
|

A Holistic Cloud-Enabled Robotics System for Real-Time Video Tracking Application

Abstract: Abstract. Future distributed sensor fusion applications will require efficient methods of information management such as Cloud computing. Using a serverbased cloud-enabled software architecture would increase performance over hardware constraints (e.g., power, memory, and processors). In this paper, we propose a comprehensive framework for information fusion demonstrated for Cloud Robotics, which possesses user favorable features such as good scalability and elasticity. Robots are connected together to form a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…The well-known attractive features of Cloud Computing include on-demand scalability of highly available and reliable pooled computing resources, secure access to metered services from anywhere, and displacement of data and services from inside to outside the organization. In our previous research, we have been exploring and evaluating the application of Cloud computing technology in robotic systems [19], mobile telemedicine Cloud [20,21,22,23], text analytics [24] and SSA [15]. While the applications seem unrelated, we found that the system framework and Cloud side considerations are similar, with differences in application specific aspects such as data-generating sensors, data processing algorithms and potential users, etc.…”
Section: Introductionmentioning
confidence: 88%
“…The well-known attractive features of Cloud Computing include on-demand scalability of highly available and reliable pooled computing resources, secure access to metered services from anywhere, and displacement of data and services from inside to outside the organization. In our previous research, we have been exploring and evaluating the application of Cloud computing technology in robotic systems [19], mobile telemedicine Cloud [20,21,22,23], text analytics [24] and SSA [15]. While the applications seem unrelated, we found that the system framework and Cloud side considerations are similar, with differences in application specific aspects such as data-generating sensors, data processing algorithms and potential users, etc.…”
Section: Introductionmentioning
confidence: 88%
“…Among potential benefits of cloud robotics, to provide seamless and low-cost service robots is one of the most meaningful topics at the current stage. In order to simplify the problem, most cloud-based robotic systems set a very strict assumption, i.e., the resource in cloud is unconstrained [32]. As a matter of fact, most of the resources in the cloud robotics system are indeed constrained [33].…”
Section: B Current Cloud Robotic Approachesmentioning
confidence: 99%
“…They concluded that the proposed platform provides strong advantages in performance without compromising security. The DAvinCi project reported in 20 provides a platform for solving Fast SLAM as a paral- 24 present Cloud Enabled Robotics System (CERS) that allows robots to mesh together to form a local networked system. These robots can offload heavy computation tasks to the server side implementation of a cloud enabled software architecture.…”
Section: Remote Brain: Offloading Computationmentioning
confidence: 99%